International diversification in the periods of major economic changes - Gluzicka, Agata (Research Papers of Wrocław University of Economics, 2018)
Diversification is one of the most important elements considered in the process of the construction of investment portfolios. A special role is attributed to the diversification in periods of rapid changes in the financial markets. In the article, the problem of international diversification was analysed on the example of selected European, American and Asian markets. The level of diversification was assessed by various measures: Portfolio Diversification Index, Rao’s Quadratic Entropy and Diversification Ratio. In the study diversified portfolios were compared. These portfolios were constructed for the data from the periods before, during and after the last economic crisis. The conducted research showed that European markets were most diversified, regardless of the nature of the analysed period. The study also showed that strongly interrelated countries did not necessarily have strong influence on diversification
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 77-87
Keywords: diversification; Rao’s Quadratic Entropy; Portfolio Diversification Index; Most Diversified Portfolio; dywersyfikacja; kwadratowa entropia Rao; indeks dywersyfikacji portfela; portfele najbardziej zdywersyfikowane